Pad weight gain in asymptomatic continent women is far less than the current ICS definition. Issue 8 (17th September 2020) - Duffy, Megan; Axell, Richard; Nicholls, Claire; Gora, Audrey; Solomon, Eskinder; Kightley, Robert; Hamid, Rizwan; Ockrim, Jeremy L.; Pakzad, Mahreen; Greenwell, Tamsin J.
Abstract: Aims: To investigate typical pad weight gain (PWG) in asymptomatic women who have never reported any episodes of urinary incontinence. Methods: An observational study was performed by measuring the increase in weight of small sanitary pads worn by 35 healthy, female volunteers of a median age 36 (range, 23–56) years. Each pad was worn for a minimum of 5 h which is the typical maximum duration of an ambulatory urodynamics study. Results: The median duration of pad wear was 6 h (interquartile range [IQR], 5–8). The median PWG was 0.111 g (IQR, 0.047–0.255). The maximum recorded PWG was 0.621 g and the minimum was 0.012 g. PWG was not significantly affected by age, parity, years since last delivery, body mass index, or menopausal status. Conclusions: PWG over a median duration of 6 h (IQR, 5–8) is typically <0.7 g in women who are asymptomatic of urinary incontinence. Therefore, PWGs in excess of 0.7 g over a 5‐h ambulatory urodynamics study in symptomatic women are likely to be diagnostic of urinary incontinence.